Contribution of recurrent admissions in children and young people to emergency hospital admissions: retrospective cohort analysis of hospital episode statistics. Issue 9 (18th May 2015) - Wijlaars, Linda PMM; Hardelid, Pia; Woodman, Jenny; Allister, Janice; Cheung, Ronny; Gilbert, Ruth
Abstract : Objective: To examine the contribution of recurrent admissions to the high rate of emergency admissions among children and young people (CYP) in England, and to what extent readmissions are accounted for by patients with chronic conditions. Design: All hospital admissions to the National Health Service (NHS) in England using hospital episode statistics (HES) from 2009 to 2011 for CYP aged 0–24 years. We followed CYP for 2 years from discharge of their first emergency admission in 2009. We determined the number of subsequent emergency admissions, time to next admission, length of stay and the proportion of injury and chronic condition admissions measured by diagnostic codes in all following admissions. Results: 869 895 children had an index emergency admission in 2009, resulting in a further 939 710 admissions (of which 600 322, or 64%, were emergency admissions) over the next 2 years. After discharge from the index admission, 32% of 274, 986 (32%) children were readmitted within 2 years, 26% of these readmissions occurring within 30 days of discharge. Recurrent emergency admission accounted for 41% of all emergency admissions in the 2-year cohort and 66% of inpatient days. 41% of index admissions, but 76% of the recurrent emergency admissions, were in children with a chronic condition. Conclusions: Recurrent admissions contribute substantially to total emergency admissions. They often occur soon after discharge, and disproportionately affect CYP with chronic conditions. Policies aiming to discourage readmissions should consider whether they could undermine necessary inpatient care for children with chronic conditions.